Possibilities and Approaches of European Court of Human Rights and Court of Justice of the European Union in Fundamental Rights Protection in the Context of Environmental Litigation - Tímea Lazorčáková (Bratislava Law Review, 2023)
Two judicial bodies, but both without right to protect the environment established. This is also how the coexistence of the two important judicial bodies located in the European area could be briefly characterized. The European Court of Human Rights and the Court of Justice of the European Union were created for different purposes, but their jurisprudence in the area of environmental protection and the protection of people's lives and health from the negative consequences of climate change overlap more than it might seem at first sight. We find certain similarities in terms of ensuring a certain degree of protection of fundamental rights in the context of the environment. The European Court of Human Rights has a priority in terms of the protection of fundamental rights in Europe, but in the field of the environment it faces several problems. Especially when we are talking about the protection of rights for future generations, where there is no direct victim or direct violation of fundamental rights, only a very high risk of their violation. On the other hand, the Court of Justice of the European Union has a much greater assumption of effectiveness, which has the potential to change the legislation of the member states and thereby indirectly ensure the protection of people's lives and health. Recently, the activity of the European Commission has been increasing in the interest of achieving climate neutrality, and this also means greater pressure on the states in the interest of the complete and correct transposition of European regulations in the field of the environment. In case of deficiencies, the European Commission can intervene by filing a lawsuit according to Article 258 of the TFEU, and achieve the required remedy. Although, such a procedure is not primarily aimed at the protection of fundamental rights, the positive impact on their protection cannot be neglected.